2018
DOI: 10.3892/mco.2018.1715
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of laparoscopic training for gynecological malignancies using Thiel‑embalmed human cadavers

Abstract: The introduction of laparoscopic surgery has also been beneficial for patients with gynecological malignancies. In this respect, surgeons should receive related training in the context of human resource development. Hands-on training was introduced using Thiel-embalmed human cadavers (THCs) in 2014. To determine the usefulness of THCs, they were evaluated in terms of tissue color, consistency and operative tactility, among others, compared with in vivo laparoscopic training for gynecological malignancies. Hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…Indeed, most participants in our courses had attended other training courses and had significant clinical experience. However, a standardized documentation of the participants’ previous training experience and skills has not been carried out in detail in previous studies [ 29 , 30 , 42 ] and so we cannot compare our findings with other studies. Thus, it is not possible to state whether the low training effect regarding laparoscopic suturing techniques is due to the participants being already proficient in suturing, the specific set-up of our training course, or to the conditions of the body donors.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Indeed, most participants in our courses had attended other training courses and had significant clinical experience. However, a standardized documentation of the participants’ previous training experience and skills has not been carried out in detail in previous studies [ 29 , 30 , 42 ] and so we cannot compare our findings with other studies. Thus, it is not possible to state whether the low training effect regarding laparoscopic suturing techniques is due to the participants being already proficient in suturing, the specific set-up of our training course, or to the conditions of the body donors.…”
Section: Discussionmentioning
confidence: 82%
“…Undoubtedly, both Thiel´s embalming method and fresh-frozen body donors provide good tissue properties and a realistic setting [ 25 27 , 29 ]. Compared to fresh-frozen cadavers, advantages of Thiel’s method include low odor nuisance, the option for multiple reuse and no need for expensive deep-freezing facilities and time-consuming defrosting procedures [ 28 , 29 ]. However, these advantages were also achieved by using ethanol-glycerol-lysoformin fixation, e.g., low odor, optional reuse, and easy storage [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic surgery requires different skills from conventional surgery, and training programs that allow surgeons to learn such technical skills are needed. Skill-training laboratories and various simulation models have been developed, such as dry box simulators, virtual reality simulators, and animal models (3)(4)(5)(6)(7)(8)(9)(10). In Japan, the publication of the "Guidelines for Cadaver Dissection in Education and Research of Clinical Medicine" in 2012 confirmed that surgical training using cadavers is lawful, providing it is conducted under adequate supervision and appropriate rules (3,6).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, some medical universities have started to perform surgical training using human cadaver models (3). Due to their fidelity and anatomy, human cadavers are a useful resource for surgical training (4,(6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%
“…The arrival of laparoscopic techniques has created a novel paradigm for surgical training, with a new learning model and a shift towards more structured laparoscopic training programs. Trainees need to acquire and perfection new surgical skills before performing in a patient to guarantee the best quality treatment (1,2).…”
Section: Introductionmentioning
confidence: 99%